Ubiquitination and ALL: Identifying FBXO8 as a prognostic biomarker and therapeutic target - Xian, Wei; Chen, Yinting; Yu, Shuiqing; Ye, Zhitao; Zhang, Yu; Yao, Danlin (Frontiers in Immunology, 2025)
BackgroundAcute lymphoblastic leukemia (ALL) is a hematological malignancy with high survival rates in children; however, certain high-risk subtypes pose significant challenges due to poor prognosis and frequent relapse. Ubiquitination, a post-translational modification critical for protein regulation, has been implicated in various cancer processes, yet its role in ALL remains poorly understood.MethodsUsing the TARGET database, we identified molecular subtypes of ALL through consensus clustering based on ubiquitination-related genes (URGs). A nine-gene prognostic model was constructed using LASSO and Cox regression analyses. The immunological landscape variations between high- and low-risk groups were assessed using immune cell infiltration analysis and functional enrichment studies. FBXO8 was further explored through functional experiments in vitro and in vivo.ResultsFour ALL subtypes with distinct survival outcomes were identified, with Cluster D representing the high-risk group. Patients were divided into high- and low-risk groups using the nine-gene predictive model, and FBXO8 was found to be a significant protective factor. According to immune landscape analysis, high-risk groups had an immunosuppressive microenvironment that was correlated with FBXO8 expression and marked by an increase in regulatory T cells and M2 macrophage infiltration. In vitro functional assays, FBXO8 knockdown notably enhanced cell proliferation and suppressed apoptosis in ALL cells. In FBXO8-knockdown mouse models, in vivo investigations demonstrated increased tumor growth, reduced apoptosis, and diminished survival rates.ConclusionThis work identifies FBXO8 as a crucial therapeutic target and prognostic biomarker for ALL. Knockdown of FBXO8 led to the suppression of apoptosis and increased tumor growth, suggesting potential therapeutic applications. These results highlight the need for more investigation into ubiquitination-related pathways and offer important new insights into high-risk ALL.